Analisis Peran Elemen Arsitektur Vernakular Jawa terhadap Efektivitas Ventilasi Alami pada Iklim Tropis - Muhammad Syihabul Milal (Journal of Engineering and Applied Technology, 2025)
This study discusses the role of Javanese vernacular architectural elements in the effectiveness of natural ventilation in tropical climates, given Indonesia's high temperatures, humidity levels of over 70%, and high solar radiation intensity throughout the year. The research method used was a descriptive qualitative approach through literature study, field observation, and architectural element analysis, focusing on the Joglo and Limasan house typologies, wood materials, cross openings, and roof shapes. The results show that the combination of structural elements, strategic openings, building orientation, and passive ventilation can reduce interior temperatures by 3–3.3°C, maintain humidity, and improve air quality without relying on mechanical systems. The discussion emphasizes the synergy between local wisdom and bioclimatic principles in creating thermal comfort, while also serving as a reference for sustainable modern tropical design. In conclusion, the integration of traditional elements and natural ventilation strategies effectively supports comfortable, healthy, and energy-efficient tropical housing.